Classical reception and children's literature: Greece, Rome and childhood transformation - Lovatt, Helen Verini (I. B. Tauris, 2018)
This volume presents research on the reception of the Classical world in children's literature, from the nineteenth century to the present day. It brings together contributions from scholars in Classics, English, History of Art and Education to discuss the ways that Classics is transformed by writing for children and childhood is transformed by Classics and ideas about Greece and Rome. The main theme is transformation and several articles focus on Metamorphoses, both those of Ovid and those of Apuleius. The volume also explores how Classical education is represented and how education forms an important theme in literature for child audiences that deal with Greek and Roman themes. It includes the voices of authors and child readers to explore the limits of what it means to write for children. It begins with a case study on Michael Cadnum, and moves on to a section on Changing Times which looks at broad studies of Aesop and Roman Britain; section two looks at mythology, particularly Pan, Arachne and Narcissus, and explores the interaction between text and image; section 3 looks at didactic Classics, school stories, Edward Lear and Caroline Lawrence; two articles on Ovid and Apuleius in C. S. Lewis lead into an afterword which explores the reading habits of two contemporary children.